Dexamethasone for Prevention of Postoperative Shivering: A Prospective Clinical Study (KYAMC Journal, 2019)
Background: Postoperative shivering (POS) is one of the common problems following general anesthesia and with different unpleasant and stressful consequences for patients. Hence, its proper management is necessary for both prevention and treatment.Objectives: The aim of this study was to find out the prophylactic effect of intravenous dexamethasone in preventing postoperative shivering after general anesthesia.Materials and methods: Patients aged from 20 to 50 years were taken for study whohas been scheduled for elective surgery under general anesthesia and they were randomized into two equal groups. Group I (Dexamethasone group) received intravenous dexamethasone and group II received intravenous saline (Placebo group). Shivering was determined postoperatively and analyzed statistically.Results: Patients who had received intravenous dexamethasone, experienced a significantly lower incidence of postoperative shivering compared to placebo group (15% versus 55%, p